2021
DOI: 10.1186/s12894-021-00802-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of biodegradable-antireflux heparine coated ureteral stent: animal model study

Abstract: Background Double J ureteral stents are widely used on urological patients to provide drainage of the upper urinary tract. Unfourtunately, ureteral stents are not free from complications, as bacterial colonization and require a second procedure for removal. The purpose of the current comparative experimental study is to evaluate a new heparin-coated biodegradable antireflux ureteral stent (BraidStent®-H) to prevent urinary bacterial colonization. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…The optimal combination of polymers and copolymers in the stent is determined by the requirements of their placement in the upper urinary tract [ 10 , 20 ]. The main current limitations to the development of biodegradable ureteral stents (BUS) are related to the control of the degradation rate and the size of the degradation fragments [ 10 , 20 , 21 , 22 , 23 ]. For this reason, a combination of polymers and copolymers with different degradation rates (always with degradation mainly by hydrolysis when placed in urine) are chosen to produce BUS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal combination of polymers and copolymers in the stent is determined by the requirements of their placement in the upper urinary tract [ 10 , 20 ]. The main current limitations to the development of biodegradable ureteral stents (BUS) are related to the control of the degradation rate and the size of the degradation fragments [ 10 , 20 , 21 , 22 , 23 ]. For this reason, a combination of polymers and copolymers with different degradation rates (always with degradation mainly by hydrolysis when placed in urine) are chosen to produce BUS.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of this new design (BraidStent-SF-MMC1 or -2) with other biodegradable ureteral stents made of PGA and Glycomer TM 631 have been experimentally evaluated in the literature [ 21 , 22 , 23 ]. We found that, as with Braidstent groups 1 and 2 in the current study, coating with SF and MMC caused a significant reduction in the rate of ureteral stent degradation, from 6–7 weeks to 13–14 weeks ( Figure 5 ) [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heparin coating allows for an early reduction in bacterial colonization. However, this effect is limited in the long term [55]. Champagne et al examined the degradation of zinc compounds in artificial urine to try to circumvent the limitations of alloys based on iron and magnesium regarding biocompatibility and controlled degradation under physiological conditions.…”
Section: Current Methods For Reducing Encrustation and Biofilm Formationmentioning
confidence: 99%
“…To perform the in vitro study, 24 fragments of a 10 mm long BraidStent ® (JUMISC, Cáceres, Spain) biodegradable ureteral stent were made by combining biodegradable polymers and copolymers—Glycomer™ 631 and polyglycolic acid (PGA), at a ratio of 54% and 46%, respectively [ 12 , 13 , 14 ]. Two 0.17 mm thick threads of Glycomer™ 631 and two 0.14 mm thick threads of PGA, all 10 mm long, were used to manufacture the stent.…”
Section: Methodsmentioning
confidence: 99%